Breakfast Consumption Pattern and Cognitive Skills of School Children in Relation to the Parental Components - Suvarna Maigur; Manjula Patil (Archives of Current Research International, 2025)
Breakfast provides body and brain with fuel and it differs qualitatively from eating after overnight fast during sleep. A study was conducted to examine the influence of parental factors on breakfast consumption and cognitive skills of higher primary school children at University of Agricultural Science Dharwad (2021-22). Study sample comprised of 60 children from rural and 60 children from urban (9-13 years) in Dharwad district who attended higher primary school (5th, 6th and 7th). Breakfast consumption and demographic information was assessed by using self-structured questionnaire. Socio economic status developed by Aggarwal et al,2005 was used to assess parent education and parent occupation. The cognitive skills of children were assessed by using Wechsler’s Intelligence Scale for School Children (WISC-III). Results revealed that, children with younger age parents had higher cognitive scores compared to older age parents, parent’s education and occupation showed significant association and differences with regular and irregular breakfast consumers. Thus, study results indicate that, there is a need for guidance/ counseling, orientation programme to children and their parents to encourage their regular breakfast consumption.